Modeling sample selection for durations with time-varying covariates, with an application to the duration of exchange rate regimes - Frederick J. Boehmke; Christopher M. Meissner (University of California, Department of Economics, 2009)
We extend existing estimators for duration data that suffer from non-random sample selection to allow for time-varying covariates. Rather than a continuous-time duration model, we propose a discrete-time alternative that models the effects of sample selection at the time of selection across all subsequent years of the resulting spell. Properties of the estimator are compared to those of a naive discrete duration model through Monte Carlo analysis and indicate that our estimator outperforms the naive model when selection is non-trivial. We then apply this estimator to the question of the duration of monetary regimes and find evidence that ignoring selection into pegs leads to faulty inferences.
Keywords: 330